Quand l’air reprend son souffle - Zoé Brioude (Ambiances)
On Philippe Quesne’s stage, human hierarchies and linearity of action are destructured: anthropocentrism no longer reigns and the scenic world exists for itself. Things and bodies can release ecstasies, to form what Böhme called aesthetic atmospheres. Neither objective nor subjective, they blur the boundaries between subjects and objects, actors and acted, and open up a new materialism that resolutely takes the side of matter against economical and anthropocentric materialism in the context of the ecological crisis. In this reconfigured ontology, the utterly Rossetian, idiotic characters that populate the Vivarium Studio take on an airy (Philippe Quesne’s favourite element) cheerfulness that allows them to get as close as possible to reality and its tragic truth: reality is all that exists and nothing more. An author of science-fiction sets the tone: “The future that awaits us is the one we create. You’d better believe it.”. The paradoxical compromise between a metaphysical and a materialist approach to the real, which we refer to as the metaphysics of the sensible, is the symptom of an art that has renounced transcendence and must now attune to the twilight of a fight against the gentle ending of the world.